Study on strength and durability properties of bio-concrete - Ashok Varma, B; Chandra Sekhar, G (International Journal of Engineering and Technology, 2018)
Concrete is very vulnerable to cracking which allows chemicals, salts and water which initiates the corrosion and reduces the life of concrete structures. So it is better to adopt a self-repairing technique which can reduce the fissures and cracks. Bio-concrete is one of the remedial techniques. In this project Bio-concrete is prepared under the grade of concrete M20 by using various amounts of bacteria (Bacillus subtilis) to enhance the strength and durability properties of concrete. The compressive strength and tensile strength of concrete were found .The durability studies are also carried out by using concentered H2SO4 for both conventional and bio-concrete specimens exposure to 28 days and it showed that bio-concrete gave better Improvement comparatively.